Parks and nature reserves: the driving force of ecotourism - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Nature reserves and national parks were originally conceived as a means of preserving flora and fauna in their natural habitat. Now they are often seen as a means of generating more lucrative activities, particularly those linked to hunting, and to...